The Effect of Cash Management System Quality on Customer Retention Loyalty at Bank Syariah Indonesia KC Rantauprapat - Dalimunthe, Maya Oktavia; Sugianto; Anggraini, Tuti (Yayasan Sinergi Kawula Muda, 2024)
This research aims to find out whether the quality of the Cash Management System at Bank Syariah Indonesia KC Rantauprapat influences customer loyalty. Participants in this research were customers of Bank Syariah Indonesia KC Rantauprapat. Quantitative research is the methodology used. Researchers only selected a sample of 60 respondents, so the selection was carried out using a total sampling technique. Validated and reliable questionnaires were included in the data collection methods. Simple linear regression, classical assumption test, F hypothesis test, t hypothesis test, and coefficient of determination are data analysis methods used to answer hypotheses. The results of the research carried out show that the t value calculated for the Quality of the Cash Management System (X) is 6.832. With this value greater than t table (2.002). Thus, Ha is accepted and Ho is rejected in testing the research hypothesis. Cash Management System has a significant influence on fund transfer decisions, because Cash Management System contributes to fund transfer decisions by Bank Syariah Indonesia KC Rantauprapat customers. The bill payment feature allows customers to make payments such as telephone, electricity, cellular operator or insurance bills, while delivery orders can be used to make payments for shipping goods.